Series and Parallel Elastic Actuation: Impact of natural dynamics on power and energy consumption. (August 2016) - Verstraten, Tom; Beckerle, Philipp; Furnémont, Raphaël; Mathijssen, Glenn; Vanderborght, Bram; Lefeber, Dirk
Abstract: This paper provides a detailed analysis of the power and mechanical/electrical energy consumption of Series Elastic Actuators (SEAs) and Parallel Elastic Actuators (PEAs). The study is done by imposing a sinusoidal motion to a pendulum load, such that the natural dynamics automatically present itself in the power and energy consumption. This allows to link the actuators' dynamics to their loss mechanisms, revealing interesting characteristics of series and parallel elastic elements in actuator designs. Simulations demonstrate that the SEA and PEA allow to decrease both peak power and energy consumption, provided that the stiffness of their elastic element is tuned properly. For the SEA, both are minimized by tuning the elastic element to the antiresonance frequency of the actuator. For the PEA, peak power is minimal at the link's resonance frequency, but the optimal stiffness for minimal electrical energy consumption cannot be determined by a theoretical resonance and needs to be calculated using a complete system model. If these guidelines are followed, both types of elastic actuators can provide significant energetic benefits at high frequencies. This was confirmed by experiments, which demonstrated energy reductions of up to 78% (SEA) and 20% (PEA) compared to rigid actuators. Highlights: Peak power of the PEA is minimal at the link's resonance frequency. Calculation of minimal electrical energy for the PEA requires system (loss) models. Peak power and energy of the SEA are minimal at antiresonance. SEA and PEA are only more efficient than rigid actuators at high frequencies. In experiments on a pendulum, a properly tuned SEA consumed less than a PEA.